Granting of right of use of water resources in the Alto Piranhas River Course in the Sertão da Paraíba - Sousa, Francisca Rozângela Lopes de; Santos, Valterlin da Silva; Oliveira, Mayara Muniz de; Vale, José Robson Lopes do; Pessoa, Mariana Ferreira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The water uses rights concession is important for the controlled and correctly uses of water resources. The objective of the work was to perform a research of the water uses rights concession as well as to prepare a diagnosis of such concession region of the High Piranhas River, Paraiba State. For the accomplishment of this study, initially, it was realized out a survey of the water concessions issued in the region on the website of the Executive Agency for Water Management of the Paraiba State followed by an interview with the Agency's manager. The results allowed identifying the real situation of water users in the region, to the point that the majority of users do not have a water concession or they are overdue, being the main use for irrigation and rural supply; the users with water concession consume on average 23 m³/hour and about 38% of registered users consume more than 2 m³ / hour, that is, they can have water concession.